2020
DOI: 10.20517/2574-1225.2020.63
|View full text |Cite
|
Sign up to set email alerts
|

Robotic vs. laparoscopic major hepatectomy

Abstract: The introduction of laparoscopic technology and surgical robots in hepatobiliary surgery in the 1990s and 2000s, respectively, has dramatically revolutionized the field. Even though laparoscopic and robotic major hepatectomy was slower to adopt compared to minimally-invasive minor hepatectomy, the number of major hepatectomies performed with both approaches worldwide has significantly increased and is still rising. Despite the few comparative studies between laparoscopic and robotic major hepatectomy, most stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The gradual and widespread adoption of minimally invasive (MI) liver surgery throughout the world has generated data showing equivalent or even superior outcomes after MI minor and major hepatectomy versus open hepatectomy. [4][5][6][7][8] Therefore, the growing surgical experience allowed several groups to perform laparoscopy-assisted, pure laparoscopic, and robotic living donor hepatectomy in comparison to the conventional open approach (LALDH, PLLDH, RLDH, OLDH). [9][10][11][12] In fact, several international consensus conferences have deemed PLLDH a standard practice for LLS and eligible for LH and well-selected RH cases, while RLDH was still deemed to be in its early phase compared with PLLDH, yet can be an acceptable alternative in experienced high-volume centers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gradual and widespread adoption of minimally invasive (MI) liver surgery throughout the world has generated data showing equivalent or even superior outcomes after MI minor and major hepatectomy versus open hepatectomy. [4][5][6][7][8] Therefore, the growing surgical experience allowed several groups to perform laparoscopy-assisted, pure laparoscopic, and robotic living donor hepatectomy in comparison to the conventional open approach (LALDH, PLLDH, RLDH, OLDH). [9][10][11][12] In fact, several international consensus conferences have deemed PLLDH a standard practice for LLS and eligible for LH and well-selected RH cases, while RLDH was still deemed to be in its early phase compared with PLLDH, yet can be an acceptable alternative in experienced high-volume centers.…”
Section: Introductionmentioning
confidence: 99%
“…The gradual and widespread adoption of minimally invasive (MI) liver surgery throughout the world has generated data showing equivalent or even superior outcomes after MI minor and major hepatectomy versus open hepatectomy 4–8 . Therefore, the growing surgical experience allowed several groups to perform laparoscopy-assisted, pure laparoscopic, and robotic living donor hepatectomy in comparison to the conventional open approach (LALDH, PLLDH, RLDH, OLDH) 9–12 .…”
Section: Introductionmentioning
confidence: 99%
“…Since then, liver surgeons have attempted to expand the application of robotic systems in hepatic resection. Several studies have reported that robotic hepatectomy (RH) is both safe and feasible (9)(10)(11)(12)(13)(14). Although operation times are longer for RH than for LH, a recent meta-analysis demonstrated that the postoperative complications and oncologic outcomes of RH are comparable to those of LH (15).…”
Section: Introductionmentioning
confidence: 99%